The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/gj.3631
|View full text |Cite
|
Sign up to set email alerts
|

A hidden crust beneath the central Urumieh‐Dokhtar Magmatic Arc revealed by inherited zircon ages, Tafresh, Iran

Abstract: Laser ablation ICP‐MS U–Pb dating on inherited zircons from Neogene volcanic rocks of the Tafresh area in the central part of Urumieh‐Dokhtar Magmatic Arc (UDMA) yielded Paleoproterozoic, Late Neoproterozoic–Early Cambrian, Carboniferous, and Cretaceous ages. These ages improve our understanding of the geodynamical evolution of central UDMA. The 2,379 Ma age (i.e., Paleoproterozoic) is the oldest age reported in the central UDMA and is similar to the age of detrital zircons from Central Iran. The Paleoproteroz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Cretaceous volcano-sedimentary sequences are the oldest rock units that crop out near to the study area; however, the presence of older crustal rocks is suggested by the inherited zircons retrieved from volcanic rocks in the present study. Palaeoproterozoic, Neoproterozoic-early Cambrian, Palaeozoic and Mesozoic ages (Hassanzadeh et al 2008;Chaharlang & Ghorbani, 2020) obtained for inherited zircons from igneous rocks imply the presence of older crustal materials underlying the Alborz, Sanandaj-Sirjan and Central Iran tectonomagmatic zones. Igneous rocks in the study area entirely comprise Tertiary magmatic rocks, including Eocene, Oligocene and Miocene rock units (Figs 2, 3).…”
Section: Geological Overviewmentioning
confidence: 95%
See 2 more Smart Citations
“…Cretaceous volcano-sedimentary sequences are the oldest rock units that crop out near to the study area; however, the presence of older crustal rocks is suggested by the inherited zircons retrieved from volcanic rocks in the present study. Palaeoproterozoic, Neoproterozoic-early Cambrian, Palaeozoic and Mesozoic ages (Hassanzadeh et al 2008;Chaharlang & Ghorbani, 2020) obtained for inherited zircons from igneous rocks imply the presence of older crustal materials underlying the Alborz, Sanandaj-Sirjan and Central Iran tectonomagmatic zones. Igneous rocks in the study area entirely comprise Tertiary magmatic rocks, including Eocene, Oligocene and Miocene rock units (Figs 2, 3).…”
Section: Geological Overviewmentioning
confidence: 95%
“…A few Palaeoproterozoic zircons indicate the incorporation of older crustal materials (i.e. those derived from the African craton and supplied by Central Iran sedimentary beds) in the late Neoproterozoicearly Cambrian magmatism (Chaharlang & Ghorbani, 2020). The presence of 1870 Ma detrital zircons in the Tashk Formation siliciclastic rocks (Ramezani & Tucker,Fig.…”
Section: Degree Of Crustal Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another criticism that may arise against this article is extending the volcanic activity in the Urumieh-Dokhtar Magmatic arc (UDMA) to Jurassic -Lower Cretaceous; while its exposed rocks not older than Paleocene in Iran. My justification is shown in three facts: the first is the recent conclusion of Chaharlang and Ghorbani (2020) [73] that a volcanic activity occurred on UDMA during the Cretaceous (106 m.y.). The second is the extensive erosion of the rocks of the UDMA during the Jurassic-Early Cretaceous due to the availability of large accommodation space for sediments transport to the deep basin (Fig.…”
Section: The Most Serious Challenge To This Studymentioning
confidence: 97%